New Evidence of the Semi‐Aquatic Nimba Otter Shrew (Micropotamogale lamottei) at Mount Nimba and in the Putu Range of Liberia – Uncertain Future for an Evolutionary Distinct and Globally Endangered (EDGE) Species in the Face of Recent Industrial Developments. (April 2016) - Decher, J.; Gray, C.R.; Garteh, J.C.; Kilpatrick, C.W.; Kuhn, H.J.; Phalan, B.; Monadjem, A.; Kadjo, B.; Jacquet, F.; Denys, C.
Abstract: New records of the endemic semi‐aquatic Nimba Otter Shrew Micropotamogale lamottei (Tenrecidae, Potamogalinae) were obtained during recent Environmental Impact Assessments (EIAs) in Liberia. We discuss the future of this Evolutionary Distinct and Globally Endangered (EDGE) species in the face of large‐scale landscape transformations. In an attempt to assess genetic diversity and genetic differentiation of M. lamottei throughout its distributional range, we examined two mitochondrial loci (cytochrome b and 12S rRNA) from five samples of Nimba Otter Shrews at three localities in Liberia and compared the 12S sequences with a GenBank sequence from Côte d'Ivoire. While all six individuals examined had unique mitochondrial haplotypes, the sequence divergence among these haplotypes was less than 1 %. However, the FST values indicated substantial differences between East Nimba and the other two populations. Recognizing that the genetic results are based on very small samples, the data suggest that the three populations experienced sufficient gene flow in the past, preventing sequence divergence, but currently there is substantially reduced gene flow with the East Nimba population. More targeted surveys in the Upper Guinea Region are recommended for this elusive species using aquatic traps in combination with an environmental DNA (eDNA) approach.